Past and present taxonomy of the Liolaemus lineomaculatus section (Liolaemidae): Is the morphological arrangement hypothesis valid? - Breitman, Maria Florencia (2013)
Twenty-one species of lizards are included in the southernmost clade of South America, the Liolaemus lineomaculatus section. There are two hypotheses of species-grouping within this section, one based on morphological similarities and the other based on molecular phylogenetic relationships; although discordant, both are in use. The 'morphological arrangement hypothesis', which sorts the species of the section in three groups, was proposed ~30 years ago; however, despite taxonomic changes and almost doubling the species diversity of this section since then, the hypothesis has never been tested. Here, we (1) present an updated chronological review of taxonomic changes, species descriptions, morphological groups, and genetic clades proposed for the L.lineomaculatus section, and (2) evaluate the accuracy of the 'morphological arrangement hypothesis'. We show that the traditional practice of classifying 11 of these species in two of the three traditional morphological groups of the section (Liolaemus kingii and Liolaemus archeforus), which is not supported by molecular data, is also not supported by morphological data, and therefore should be abandoned; we suggest referring to this group of species as the L.kingii group. We characterized the Liolaemus magellanicus group based on morphology, and extend the previously published morphological characteristics of the L.lineomaculatus group. Finally, we comment on future prospects for studies of sexual dimorphism and its possible ecological implications. This paper provides a critical synthesis of our understanding of the morphological and phylogenetic patterns within the L.lineomaculatus section and presents a useful framework for future tests of taxonomic hypotheses and physiological, behavioural, and evolutionary questions within this section.